Paradiplomacia no Brasil: uma abordagem sobre a inserção internacional de municípios paraibanos a partir do Programa Plano Diretor - Morais, Maria Cezilene Araújo de (2011)
The contemporary International Society comprises a number of international actors whose interaction level among them has resulted in the State´s loss of traditional centrality. The primary objective of this work is to analyze the role of Paradiplomacy in International Relations, mainly that played in Paraiba municipalities such as Alagoa Grande, Cabaceiras, Livramento, and Sertãozinho, where subnational units are known to share interests to conduct foreign policy of the States. The general view of the Paradiplomacy phenomenon as well as its development in the Brazilian context are essential to understand the Projeto-Cidade and the role of the Plano Diretor resulting from the municipal foreign policy with international insertion. This work used theoretical reference of Soldatos (1990), Duchacek (1990), Paquin (2004), Castells & Borja (1996), and Prieto (2004) as bibliographic documentary source of research as well as institutional sites on the Internet to collect primary data. The present study concluded that the autonomy level of subnational units has revealed important paradigmatic change capable of generating particularities to conduct traditional foreign policy in Brazil.